Role of oxidative stress on acute ischaemic stroke - Ismail Setyopranoto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
After the onset of a stroke, blood flows disrupted in areas affected by vascular occlusion limit the delivery of oxygen and metabolic substrates to neurons causing ATP reduction and energy depletion. The glucose and oxygen deficit that occurs after severe vascular occlusion is the origin of the mechanisms that lead to cell death and cerebral injury caused of oxidative stress. Oxidative stress constitutes mechanism of injury of many types of disease processes. On oxidative stress occurs on the increase in ROS and RNS. This paper will discuss about cerebral ischemia that causes activation of ROS and RNS, also the mechanisms that play a role in cell death after cerebral ischemia, for example the role of phospholipase, Haber-Weiss reaction, and lipid peroxidation. It is also described about anti-oxidants to fight free radicals, for examples glutathione peroxidase, catalase and superoxide dismutase.